Legal Measures to Protect Platform Workers: A Case Study of Food Rider - Apiwan, Apinnaporn; Pichetworakoon, Arachamon (CRRU Law, Political Science and Social Science Journal, 2025)
Currently, the number of platform workers in Thailand has increased, especially food riders. The work of platform workers is different from general work. There are issues legal status, compensation, rights and welfare of work. The author investigated legal measures to protect platform workers in Thailand. It was found that the current labor law cannot be efficiently enforced to the issue of platform workers: A case study of food rider. However, legal measures have been taken to resolve this issue in several ways, the drafting of the Independent Labor Protection Act and the enactment of the Royal Decree on Digital Platform Service Businesses That Must Be Notified B.E. 2565. The author is of the opinion that are still many problems. Therefore study the concepts and theories, legal measures to protect platform workers of the International Labour Organization, the United Kingdom, the State of California, the United States, the Kingdom of Spain and the European Union. Due to organizations or groups of countries have concepts and theories, legal status, rights and welfare that are appropriate for platform workers, which can be appropriately applied to the food riders in Thailand. Consequently, the author is of the opinion that legal measures to protect platform workers: A case study of food rider in Thailand should consist of 2 measures: 1. Short-term measures: Amendments under the Labor Protection Act B.E. 2541 (1998), Section 22, which adds a royal decree specifying work that requires labor protection differently from the Labor Protection Act B.E. 2541 (1998), by issuing a ministerial regulation for food riders; and 2. Long-term measures: Issuing a royal decree-level law specifically for food riders according to the Independent Labor Protection Act draft to to determine status rider rights and welfare according to labor standards.